The Production of Renewable Fuels Sago Dregs and Low-Density Polyethylene by Pyrolysis and its Characterization - Jahiding, M; Mashuni, Mashuni; Handayani Hamid, Fitri; Sitti Ilmawati, Wa Ode; Hamdana, Renaldi (Science and Technology Indonesia, 2024)
Biomass has been suggested as a sustainable alternative to substitute fossil fuels. Based on the pyrolysis method, the biomass would be converted into energy through decomposition by thermal degradation under an inert atmosphere, resulting in charcoal, liquid, and gas products. The quality of oils is effectively enhanced through the pyrolysis of lignocellulosic biomass and plastic due to the facilitation of deoxygenation by plastics. This study investigates the impact of incorporating low-density polyethylene (LDPE) plastic in co-pyrolysis with sago dregs (SDs) waste. Pyrolysis of SDs and LDPE mixtures with ratios of 5:1, 4:2, 3:3, 2:4, and 1:5 at various temperatures of 375°C, 425°C, and 475°C. The maximum oil yield obtained for SDs and LDPE pyrolysis was 44.94%. The calorific value (CV) of all observed compositions is a minimum of 10,579.57 kcal kg-1 and a maximum of 11,545.21 kcal kg-1. The gas chromatography-mass spectroscopy (GC-MS) analysis confirmed the interaction between SDs and LDPE on co-pyrolysis. The addition of LDPE will produce rich aliphatic and aromatic compounds, like the proportions of alkanes (45.53%), alkenes (30.62%), alcohol (0.4%), and benzene (17.68%). Co-pyrolysis of SDs and LDPE promotes enhanced oil production by reducing oxygenated compounds and increasing hydrocarbon compounds.